محددات سعر الصرف الحقيقي للدينار الليبي، دراسة تحليلية قياسية عن الفترة 1970-2010 - الزروق احمد هويدي (Scientific Journal of University of Benghazi, 2020)
The main objective of the research is to study the long-run relationship between the real exchange rate of the Libyan dinar and its basic determinants during the period 1970-2010. To achieve this goal, the cointegration test was used based on the ARDL approach. The Dickey Fuller test (ADF) was also used to test the unit root of the variables and its findings indicate that all variables (openness, government expenditure, investment, technical progress, and terms of trade) in the estimated model are stable in their first differences, all of which were leading to a appreciate Real exchange rate in the long-run, and statistically significant, except for the terms of trade. Also, the error correction model was applied to estimate the short-run relationship and the results indicate that the error correction term is negative, statistically significant, and its value is somewhat high and is about - 0.60 and this indicates that, about 60% from disequilibrium in the previous year, is corrected in the following year, on each shock.